Analisis Kesalahan Siswa SMK dalam memecahkan Masalah Literasi Matematis pada Bangun Ruang - Sopian Lukman; Luvy Sylviana Zanthy (IKIP Siliwangi, 2019)
This research was conducted with the aim of describing the mistakes made by students in solving the problem of mathematical literacy. The research method used is descriptive qualitative. Data obtained through written tests consisting of 4 questions about mathematical literacy skills obtained 58% of students were able to master the problem of mathematical literacy, so that 42% of students were unable to master the problem of mathematical literacy skills. The average score of students is 34.29 with the highest value of 50 and the lowest value is 16 of the total maximum value 55. From the results of the analysis carried out on student answers, there are several mistakes made by students when completing the problem, namely: not systematic; Wrong in using formulas; Many do not use units; Wrong in writing units; Unable to interpret questions; Wrong and conclude the results of the settlement; Not complete in completion.